2017
DOI: 10.1007/s41664-017-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Determination of Negative Air Ions

Abstract: This review intends to cover a range of brief description of the generation mechanisms, the determination of the concentration, and the identification of negative air ions (NAI). This is divided into two parts: (i) it pays attention to the generation of NAI, which contains natural and artificial methods. According to the variation of energy in the environment, different methods based on natural generation are introduced in detail. As for artificial generation of NAI, corona discharge is dominantly elaborated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Because the oxygen molecule has a relatively strong electrical affinity, it can obtain electrons in preference to other molecules in the air under the same conditions, thereby forming a negative oxygen ion [4][5][6]. These negative oxygen ions are the main components of NAIs; thus, NAIs are sometimes called negative oxygen ions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Because the oxygen molecule has a relatively strong electrical affinity, it can obtain electrons in preference to other molecules in the air under the same conditions, thereby forming a negative oxygen ion [4][5][6]. These negative oxygen ions are the main components of NAIs; thus, NAIs are sometimes called negative oxygen ions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many NAI generators release ozone, including well-known brand ionizers [19][20][21][22][23]. Lin et al [24] found out that artificial NAIs also generated byproducts of noxious gas such as ozone and nitric oxide, and discovered that PAIs act on certain activities such as exciting sympathetic nerves, leading to a harmful impact on human health.…”
Section: Introductionmentioning
confidence: 99%
“…Beta particles released from radioactive elements, emit electrons that bind to oxygen molecules (O 2 ), resulting NAI (O 2 -) formation. Ionizing radiation usually generates more small negative ions in the air 29 .…”
mentioning
confidence: 99%
“…As secondary natural physical ionizing agents (or generation mechanisms), include: shearing of water droplets (waterfall, rainfall, steam, mist -Lenard Effect), hot spring nascent, UV rays, sunlight, photosynthesis (forest), photoelectric emission, lighting excitation, electricity (corona discharge), electrostatic force, aurora borealis, cave, mountain, rapid flow of great air volumes over a land mass (Fohn, Sharav, Santa Anna), wind (sand and snow friction) [29][30][31][32][33][34] .…”
mentioning
confidence: 99%
See 1 more Smart Citation